(untitled) (Research, Society and Development, 2021)
Chikungunya is an infectious tropical disease caused by Chikungunya virus (CHIKV), an RNA virus that belongs to the alphavirus genus of the family Togaviridae. It is a mosquito-borne viral disease transmitted by bites of Aedes aegypti and Aedes albopictus, most commonly. The disease evolves in three stages: acute, subacute and chronic. The chronic phase begins after 3 months of initial symptoms. Myalgia is one of the most prevalent symptoms in the disease and may be intense. In the literature, some Myopathy cases secondary to Chikungunya in acute phase were described, but few have been reported in the chronic disease. We present a case of a female patient, who developed progressive muscular weakness due to dermatomyositis in 2016 after 2 years of infection with CHIKV.